Polyphenolic Profile, Sugar Consumption and Organic Acids Generation along Fermentation of Infusions from Guava (Pisidium guajava) by the Kombucha Consortium - Nuria Elizabeth Rocha-Guzmán, Martha Rocío Moreno-Jiménez,; José Guadalupe, Rutiaga-Quiñones,; Juan Antonio Rojas-Contreras, Daniela Medrano-Núñez,; José Alberto Gallegos-Infante, Rubén Francisco González-Laredo (Recent Research in Science and Technology)
The kombucha beverage is typically prepared from black tea, sweetened with sucrose, inoculated with previously fermented liquid broth and/or tea fungus pellicle, and incubated. Alternative sources have been used for kombucha beverages. Guava leaves have been used for long time as traditional medicine. It is found in many commercially available botanical supplements in form of decoction, milled and used as comprises. They are rich in polyphenolic compounds. Several changes are produced during fermentation of the beverages. The main objective of the present work is to characterize fermentation process of guava leaves infusions by kombucha and studying possible chemical changes in their polyphenolic profile. Infusions from guava leaves were prepared and fermented by the kombucha consortium. The pH, titrable acidity, polyphenolic compounds, sugar consumption, organic acid along the fermentation was made by UPLC-ESI-MS. Kombucha from Camellia sinensis (CS) was made as a control. Higher rate of sucrose consumption was observed for Kombucha made with CS, also, higher production of organic acids (acetic and succinic acid) was observed too. Both behaviors were related to the content of glucose. The flavan-3-ols were diminishing along the fermentation time, with the exception of epigallocatechin in Camellia sinensis, Flavan-3-ol content in Guava leaves was low. Higher content of dicaffeoyl quinnic acid was observed for both systems in special for CS, falling after a maximum peak; minor constituents of hydroxycinnamic acids were stable along the fermentation for both systems.